Computation of Filament Winding Paths with Concavities and Friction. (December 2021) - Li, Hang; Sueda, Shinjiro; Keyser, John
Abstract: We introduce an efficient method to support generation of geometric winding paths on parametric shapes. Filament winding is a technology for producing composite materials by winding resin-infused fibers around the underlying model. While filament winding is a long-standing manufacturing method, only a few shapes, primarily cylinders, have been manufactured in practice. Extending this to a broader range of parametric surfaces is desirable. For convex objects without friction, generating a winding path over a model is equivalent to finding a locally geodesic path on the surface. We propose a physically-based method ideally suited for generating these geodesics, and show how it can be augmented to incorporate friction in the simulation process. For non-convex objects, it is important to correctly handle the bridging of filaments across local concavities. We therefore propose an efficient method for lifting a filament from and returning it to a surface, within the same simulation framework. We demonstrate how this method forms the basis for an end-to-end system that designers can use to create, visualize, and redesign winding paths for a variety of shapes. Highlights: We present a new approach for finding feasible winding paths across arbitrary parametric surfaces. We adopt a physics-based model of the filament motion under tension that is ideally suited for filament winding. We show incorporation of friction in the filament behavior model. We present a method for dealing with bridging behavior across concave areas within the same framework. We demonstrate an end-to-end design and analysis system for filament winding.